Introducing .NET 6 : getting started with Blazor, Maui, Winui3, desktop development, and containers - Vermeir, Nico (Apress, 2022)
Welcome to .NET 6, Microsoft's unified framework that converges the best of the modern and traditional .NET Framework. This book will introduce you to the new aspects of Microsoft's fully supported .NET 6 Framework and will teach you how to get the most out of it. You will learn about the progress to one unified .NET, including MAUI and the revival of desktop development. You will dive into Roslyn, Blazor, CLI, Containers, Cloud, and much more, using a "framework first" learning approach. You will begin by learning what each tool is, its practical uses, and how to apply it and then you will try it out on your own for learning reinforcement. And, of course, there will be plenty of code samples using C# 10. Introducing .NET 6 is aimed at .NET developers, both junior developers and those coming from the .NET framework, who want to understand everything the modern framework has to offer, besides the obvious programming languages. While you will still see a lot of fabulous C# 10 throughout the book, the focus of this learning is all about .NET and its tooling. What You Will Learn Become a more versatile developer by knowing the variety of options available to you in the .NET 6 framework and its powerful tooling Know the different front-end frameworks .NET offers, such as UWP, WPF, and WinForms, and how they stack up to each other Understand the different communication protocols, such as REST and gRPC, for your back-end services Discover the secrets of cloud-native development, such as serverless computing with Azure Functions and deploying containers to Azure Container Services Master the command line, take your skill set to the cloud, and containerize your .NET 6 app Who This Book Is For Both students and more experienced developers, C# developers who want to learn more about the framework they use, developers who want to be more productive by diving deeper into the tooling that .NET 6 brings to the fold, developers who need to make technical decisions. A working knowledge of C# is recommended to follow the examples used in the book.